Outdoor play for healthy little minds : practical ideas to promote children's wellbeing in the early years - Watkins, Sarah, 1972- (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"This essential resource is designed to help busy early years practitioners to support the mental health of young children through outdoor play. Promoting social and emotional wellbeing in childhood has never been more important and outdoor play is a crucial tool to build resilience, develop healthy relationships, and boost self-esteem. Using relatable case studies that demonstrate achievable change, the book is full of practical advice and strategies for exploring nature in both natural and man-made landscapes, and includes guidance on how to co-create inviting play spheres with children. Each chapter provides: Adaptable and cost-effective activities designed to help children feel more confident and connected to the world around them, Case studies and reflective opportunities to prompt practitioners to consider and develop their own practice, An accessible and engaging format with links to theorists, risk assessment and individual schemas Outdoor play allows young children to explore who they are and what they can do. It supports them as they learn to think critically, take risks, and form a true sense of belonging with their peers and with the wider community. This is an indispensable resource for practicing and trainee early years practitioners, reception teachers and childminders as they facilitate outdoor play in their early years setting"--
Keywords: Play; Early childhood education -- Activity programs; Outdoor education; Nature study; Child mental health; EDUCATION / General; EDUCATION / Preschool & Kindergarten